Differential Diagnosis of Intestinal Tuberculosis from Crohn's Disease and Primary Intestinal Lymphoma in China - Liu, Yun-Yan (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND/AIMS: There are many similarities and overlaps in clinical, radiological, endoscopic, and histological features among intestinal tuberculosis (ITB), Crohn's disease (CD), and primary intestinal lymphoma (PIL), and the differential diagnosis of ITB can be very challenging for clinicians. PATIENTS AND METHODS: The clinical, radiologic, endoscopic, and pathological data of 213 patients were analyzed retrospectively. According to the diagnostic criteria and exclusive criteria of ITB, CD, and PIL, 83 patients were recruited and divided into three groups, including 30 cases in the ITB group, 38 cases in the CD group, and 15 cases in the PIL group, and the medical data and statistical analysis were recorded. RESULTS: Rural patients with abdominal pain as the first symptom and with transverse ulcer and caseating granulomas were more common in the ITB group than the CD group, whereas urban patients with stool change as the first symptom, moderate or severe anemia, thickening of intestinal wall, rectal involvement, skipping distribution, prominent lymphoid aggregates, and irregular glands were more common in CD group than ITB group (P < 0.05). Young patients (age < 30 years) with fever, weakness, fatigue, abdominal mass, intestinal perforation, and emergent operation were more common in ITB group than PIL group, whereas thickening of intestinal wall, malignant lymphocytes, limited distribution, and involvement of small intestine occurred more in PIL group than ITB group (P < 0.05). CONCLUSION: The differential diagnosis of ITB from CD and PIL can be made by a combination of clinical manifestation, endoscopy, and pathological examinations.